Associations of HLA-G 3’UTR polymorphisms and increased HLA-G expression with gastric cancer susceptibility and prognosis - Ines Zemni; Daria Bortolotti; Sabrine Dhouioui; Sana Baroudi; Malek Ferjani; Inès Nasri; Yosr Zenzri; Md Ataur Rahman; Abdel Halim Harrath; Roberta Rizzo; Nadia Boujelbene; Inès Zidi (Immunobiology)
Background: Gastric cancer (GC) remains a serious health concern and is characterized by a multifactorial etiology involving both genetic and epigenetic factors. The aim of the current study was to examine the relationship between Human leukocyte antigen (HLA)-G 3’UTR polymorphisms and the expression of HLA-G in both tumor tissues and plasma samples from patients with GC in the Tunisian population. Methods: HLA-G 3’UTR polymorphisms (14pb Insertion/deletion and + 3142C/G) were identified by polymerase chain reaction (PCR) or Sanger sequencing. Plasma levels of sHLA-G (total sHLA-G, shed HLA-G1 and HLA-G5) were determined. Immunohistochemistry was used to evaluate the expression of HLA-G in tumor tissues. Results: The Del/Del genotype and Del allele frequencies were different between GC patients and healthy donors (HD) (OR [95 % CI] = 2.483 [1.070–5.410], p = 0.025 vs. OR [95 % CI] = 1.537 [0.924–2.584], p = 0.099; respectively). The C/C genotype and C allele frequencies were significantly greater in GC patients than in HD (OR [95 % CI] = 2.269[0.1.070–4.904], p = 0.033 vs. OR [95 % CI] = 1.746[1.045–2.878], p = 0.034; respectively). Interestingly, the Del/Del genotype and Del allele were significantly associated with an increased risk of GC in patients aged ≥55 years at diagnosis. HLA-G was highly expressed in GC tissues, particularly in tissues with advanced tumor invasion (T3 + T4). Compared with HD, GC patients had higher soluble HLA-G, shed HLA-G1 and HLA-G5 levels (Mann-Whitney: p = 0.001, p = 0.001 and p = 0.643, respectively). Assessment of patients' survival by Kaplan-Meier analysis indicated that the Del allele was significantly associated with reduced overall survival (OS) in GC patients at advanced stages III + IV (p = 0.043). Conclusions: These results suggest that HLA-G 3’UTR polymorphisms are associated with GC susceptibility in Tunisian population. The expression of HLA-G in both the tissue and plasma may play an important role in the development and progression of GC. Therefore, the current study supported the recommendation of investigating HLA-G 3’UTR polymorphisms in GC and indicated that HLA-G molecules could serve as promising therapeutic targets in GC.